2009
DOI: 10.1016/j.cub.2009.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dyslexia is characterized by the co-existence of visuospatial and phonological disorders in Chinese children

Abstract: Developmental dyslexia is a neurological condition that is characterized by severe impairment in reading skill acquisition in people with adequate intelligence and typical schooling. For English readers, reading impairment is critically associated with a phonological processing disorder, which may co-occur with an orthographic (visual word form) processing deficit, but not with a general visual processing dysfunction in most dyslexics. The pathophysiology of dyslexia varies across languages: for instance, unli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 10 publications
7
75
1
Order By: Relevance
“…This view is in line with several proposals consistently linking activity in the precuneus to visual imagery (Cavanna and Trimble, 2006;Fletcher et al 1995;Gardini et al 2009). It is also consistent with recent results demonstrating that normal reading children but not dyslexic children exhibited similar precuneus activation when asked to compare the physical size of two simultaneously presented Chinese characters (Siok et al, 2009). …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This view is in line with several proposals consistently linking activity in the precuneus to visual imagery (Cavanna and Trimble, 2006;Fletcher et al 1995;Gardini et al 2009). It is also consistent with recent results demonstrating that normal reading children but not dyslexic children exhibited similar precuneus activation when asked to compare the physical size of two simultaneously presented Chinese characters (Siok et al, 2009). …”
Section: Discussionsupporting
confidence: 81%
“…Crucially, as those segments are visually more complex and cannot be converted into phonemes, additional visual-orthographic analysis and visual short-term storage are mandatory. While studies investigating visual working memory as a predictor for language learning, are scarce, a couple of developmental studies have examined determinants of reading ability in Chinese children focusing primarily on visual processing skills and phonological awareness (Ho and Bryant, 1997a;Huang and Hanley, 1995;McBride-Chang and Ho, 2005;Siok and Fletcher, 2001;Siok, Spinks, Jin, and Tan, 2009;Tong and McBride-Chang, 2010). Huang and Hanley (1995) reported that visual skills such as visual form discrimination and visual paired-associate learning predicted reading in native Chinese but not in native English children.…”
Section: The Role Of Working Memory In Vocabulary Acquisitionmentioning
confidence: 99%
“…The observed large-scale network encompassed not only the known universal components of reading in occipitotemporal (4,5) and inferolateral frontal (5,8) regions, but also those brain regions previously proposed to represent culture-specific components of logographic reading, i.e., the left lateral prefrontal cortex around BA9 (15,17), left PMd (9), and bilateral PPC (13,16). Critically, however, this network showed no significant crosscultural difference between French and Chinese through its entire extent.…”
Section: Discussionmentioning
confidence: 96%
“…Reading of alphabetic scripts engages this multicomponent system with only small cultural variation depending on the degree of transparency (11) and grain size (12) of the orthographic system. However, beyond this shared left posterior network, several previous studies with normal (8,13,14) and dyslexic (15,16) Chinese participants defended a culture-specific model whereby logographic reading relies on unique cortical components (17). In a lateral prefrontal region within Brodman's area (BA) 9, just anterior to the precentral cortex, meta-analyses suggest a greater activation in Chinese compared with alphabetic readers (5,17), perhaps due to great demands on addressed phonology (17) or visuospatial working memory (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation